Some Comments on International Agreements in the Light of Obligation to Negotiate Access to the Pacific Ocean Case - Kałduński, Marcin (Studia Iuridica Toruniensia, 2020)
On 1 October 2018 the International Court of Justice (ICJ) delivered its Judgment in the case concerning Obligation to Negotiate Access to the PaSome Comments on International Agreements in the Light of Obligation 119 cific Ocean (Bolivia v. Chile). The Court considered, inter alia, the question of the existence of an international agreement between Bolivia and Chile. The determination of whether a certain instrument constitutes a legally binding agreement may have serious practical conseqences. This article discusses the true nature of international agreements in the light of the present Judgment. The contribution analyses the methodology applied by the ICJ for ascertaining the existence of a legally binding agreement and explores whether and to what extent the ICJ was influenced by the case law of the international courts and tribunals.